2016
DOI: 10.1080/23273798.2016.1151058
|View full text |Cite
|
Sign up to set email alerts
|

No place for /h/: an ERP investigation of English fricative place features

Abstract: The representational format of speech units in long-term memory is a topic of debate. We present novel event-related brain potential evidence from the Mismatch Negativity (MMN) paradigm that is compatible with abstract, non-redundant feature-based models like the Featurally Underspecified Lexicon (FUL). First, we show that the fricatives /s/ and /f/ display an asymmetric pattern of MMN responses, which is predicted if /f/ has a fully specified place of articulation ([Labial]) but /s/ does not ([Coronal], which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 56 publications
7
31
0
Order By: Relevance
“…These authors found that in cases where the deviant stimulus items presented a feature that was a mismatch when compared with those features stored for the standard, the MMN component elicited had a greater amplitude and earlier peak latency than that elicited by deviant items that were a no-mismatch . A similar asymmetry was observed by Schluter et al (2016) in the perception of fricative noise bursts for [s] and [h]: a mismatch deviant stimulus type elicited a larger MMN than a no-mismatch deviant, supporting the view that the phonological representation of [h] has no place features (see Phonological Consequences of the Phonetic Properties of [h]). In the case reported here, all the features present in our deviant [h]-less items are a subset of the features present in our standard items, which are stored for evaluation of deviance.…”
Section: Discussionsupporting
confidence: 70%
“…These authors found that in cases where the deviant stimulus items presented a feature that was a mismatch when compared with those features stored for the standard, the MMN component elicited had a greater amplitude and earlier peak latency than that elicited by deviant items that were a no-mismatch . A similar asymmetry was observed by Schluter et al (2016) in the perception of fricative noise bursts for [s] and [h]: a mismatch deviant stimulus type elicited a larger MMN than a no-mismatch deviant, supporting the view that the phonological representation of [h] has no place features (see Phonological Consequences of the Phonetic Properties of [h]). In the case reported here, all the features present in our deviant [h]-less items are a subset of the features present in our standard items, which are stored for evaluation of deviance.…”
Section: Discussionsupporting
confidence: 70%
“…Eulitz and Lahiri, 2004; Scharinger et al, 2010, 2012; Cornell et al, 2011, 2013; de Jonge and Boersma, 2015; Schluter et al, 2016). Furthermore, the more negative peak for the voiceless deviant suggests that it is the voiceless sound which is marked for English fricatives, just as Hestvik and Durvasula (2016) found for English stops.…”
Section: Discussionmentioning
confidence: 99%
“…Syllables in the 3rd position (XXY deviant) differ in their consonant voicing and place of articulation, and in their vowel height (Mioni, 1993;Kramer, 2009;Paoli, 2016). While it should be noted that whether all these phonological features have a neural representation is on itself an open debate (Hestvik and Durvasula, 2016;Politzer-Ahles et al, 2016;Schluter et al, 2016Schluter et al, , 2017, in the case of our stimuli set, the number of phonological features that change for each deviant condition is the same.…”
Section: Discussionmentioning
confidence: 98%
“…Electroencephalography (EEG) studies have identified an event related potential (ERP) known as N400, whose amplitude is inversely correlated with the semantic predictability of words in context (Ku-tas and Hillyard, 1980;Van Petten et al, 1999;Brink et al, 2001;Federmeier, 2000, 2011;Freunberger and Roehm, 2016;DeLong et al, 2005). EEG evidence has also shown that forthcoming phonemes can be predicted using syntactic (DeLong et al, 2005), semantic (Bendixen et al, 2014;Kashino, 2006;Groppe et al, 2010), phonological (Cornell et al, 2011;Hestvik and Durvasula, 2016;Schluter et al, 2016;Scharinger et al, 2016) and phonotactic information (Dehaene-Lambertz et al, 2000;Sun et al, 2015;Ylinen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%